María Zambrano y José Ángel Valente: la santidad del entendimiento (TEST Ticontre. Theory Text Translation, 2020)
The friendship between María Zambrano and José Ángel Valente went beyond a personal relationship, in spite of their subsequent estrangement. Each one found in the other an important support for his or her own interests. Their encounter needs to be understood in the context of a dialogue between the exiled republicans and the younger generations of Spaniards, like Valente, who felt the need to distance themselves from their own country as well as from the atmosphere of Franco’s dictatorship. Zambrano’s attempt at exploring a poetic reason is not far removed from Valente’s idea of poetry as knowing. As such, in a letter to the writer, we can see Zambrano’s assertion that poetry and philosophy represent the holiness of understanding. This expression should not be interpreted as a deification of reason. On the contrary, it seeks to explore the limits of understanding and language to avoid any instrumental use of them. The objective is to open a dialogue in which to explore the common territory between poetry, philosophy and mysticism. All these affinities can also be seen in common motives like emptiness or descent. This dialogue finds one of its high points in Claros del bosque, a book which contains one of the most complete examples of poetic reason, and one for which Zambrano counted on Valente’s help. Other points of reflection also emerge, such as the links between art and the sacred, or the way of looking at history, which in both figures often awakens an almost gnostic mistrust. Faced with history as sacrifice (as María Zambrano speaks of), both the philosopher and the poet seek a particular vision of time which is not to be used as an instrument of power. Time understood in a non-linear sense, and the non-instrumentalized language of poetry are thus inscribed in the realms of possibility, a return movement of which does not resign itself to the violence of history.